ANALYTICAL STUDY OF GEOMETRIC PARAMETERS OF STATIC DETERMINED HINGED SPATIAL MECHANISM OF A TUMBLING MACHINE - ZALYUBOVSKYI, MARK; PANASYUK, IGOR; KOSHEL, SERHIY; KOSHEL, GANNA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The kinematic chain of an eight-link articulated statically determined spatial mechanism with rotational and one translational kinematic pair, which underlies a tumbling machine with complex spatial motion of the working capacity, is considered. Analytical studies of the main geometric parameters of the tumbling machine have been carried out. The relationship between the corresponding geometric parameters of the eight-link articulated statically determined spatial mechanism of the tumbling machine has been determined, which makes it possible to determine rational ratios of the lengths of the mechanism links, in particular between the position of the crank and the amplitude of the reciprocating movement of the slider together with the drive shaft of the machine. An equation was obtained for the possibility of calculating the amplitude of the reciprocating movement of the slider together with the machine drive shaft. Expressions were obtained that make it possible to calculate the maximum and minimum distance between the axes of the driving and driven shafts of the machine at different positions of the moving links. Mathematical dependencies were obtained for the possibility of calculating the main design parameters of a special drive design that allows for the rotation of the machine drive shaft with simultaneous reciprocating movement, in order to ensure the pressure angles in the slider-guide kinematic pair within permissible limits. Analytical studies of geometric parameters and modeling of the design of the machine for processing parts were carried out using the “SolidWorks 2021” computer-aided design system. The obtained mathematical equations can be successfully used by machine-building industries at the stage of designing tumbling types of equipment with tanks that perform complex spatial movement.